Characterizing Reactions and Comments Associated with News on Facebook - Guimarães, Samuel; Benevenuto, Fabrício (Anais Estendidos do Simpósio Brasileiro de Sistemas de Informação (SBSI), 2021)
News consumption is increasingly done on social media websites. In this environment, all types of entities and people present themselves as news sources. These new outlets might focus on specific audiences, and some exhibit the news less objectively. Facebook is one of these platforms, which categorizes an extensive group of pages as a kind of news media. To analyze this phenomenon, it is crucial to characterize all pages that disseminate information in this ecosystem. Our main objective is to create an in-depth diagnostic of news stories and opinions, focusing on Brazilian Facebook. Our contributions are: (i) a new method to measure the political bias of Facebook pages on a given country, and (ii) a detailed characterization of a comprehensive sample of these pages.